Strategy for ILRI research on feed resources - Blümmel, Michael; Hanson, Jean; Herrero, Mario; Fernández Rivera, S.; Hansen, H.; Bezkorowajnyj, P.G. (International Livestock Research Institute, 2006)
The importance of feed in increasing livestock productivity and benefits from livestock is stressed. Four major feed resources are identified: pastures, common property resources, forests, and fallow lands; planted forages; crop residues; and concentrate and agricultural by-products. There is a scarcity of quantitative, countrywide data on the current contribution of these resources to the actual feed budget, and the likely trends in future. Systematic mapping of fodder resources is required, and seen as an integral part of feed research. Research on feed resources needs to contribute to poverty alleviation and production of global public goods, but ILRI also needs to have a competitive advantage in the research field, and the research needs to be cost efficient. Partnerships play a key role in producing synergies from diverse research efforts, and in implementation of research results and output-to-outcome processes. Collaboration between crop improvement and livestock research is seen as a key partnership in achieving the feed-related outputs of ILRI’s Medium Term Plan. Although considerable uncertainty exists in terms of quantitative contribution of specific feed resources to overall feed budget, it seems highly probable that crop residue plays, and will continue to play, a central role in sustaining mixed-crop livestock systems in resource-poor areas.